Efficient Synthesis and Characterization of Some Novel Nitro-Schiff Bases and Their Complexes of Nickel(II) and Copper(II) - Hossein Naeimi; Mohsen Moradian (Journal of Chemistry)
Synthesis and characterization of some new Schiff base ligands derived from various diamines and nitrosalicylaldehyde and their complexes of Ni(II) and Cu(II) are reported. Several spectral techniques such as UV-Vis, FT-IR, and NMR spectra were used to identify the chemical structures of the reported ligands and their complexes. The ligands are found to be bound to the metal atom through the oxygen atoms of the hydroxyl groups and nitrogen atoms of imine groups, which is also supported by spectroscopic techniques. The results obtained by FT-IR and NMR showed that the Schiff base complexes of transition metal (II) have square-planar geometry.